Xanthogranulomatous oophorosalpingitis. Case report - Reyna-Villasmil, Eduardo (2023)
Xanthogranulomatous inflammation of the female genital tract is infrequent and iseven rarer in fallopian tubes and ovaries. We present a case of xanthogranulomatousoophorosalpingitis in a 45-year-old female patient who consulted for left iliac fossapain accompanied by fever. Bimanual examination revealed a slightly enlargeduterus with a firm, non-painful left adnexal mass, adherent to the uterus and withlimited mobility. Transvaginal ultrasound evaluation showed a heterogeneous leftovarian tumor with thick and irregular walls, multiple septa and internal echoeswithout visualization of the ovary. During surgery, dense adhesions were foundfrom the mass to the pelvic lateral wall, ovarian fossa, and bowel loops. The uteruswas displaced by a thick-walled, grayish-white, cystic left adnexal tumor drainingfoul-smelling purulent fluid. The definitive diagnosis was xanthogranulomatousoophorosalpingitis. This condition is a rare inflammatory process that posesdiagnostic dilemmas. Its clinical manifestations and imaging features may mimica malignant pelvic neoplasm, so a high index of suspicion is necessary for itsdiagnosis, as a differential diagnosis in patients with complex cystic ovarian tumors.Histopathological examination is the gold standard for diagnosis.